SOCIO-ECONOMIC NATURE AND THEORETICAL FOUNDATIONS OF COMPULSORY INSURANCE - Hamrayeva F.Sh. (Antis Publisher, 2024)
Currently, it should be considered as a system of economic relations related to the provision of mandatory insurance guarantees and measures against various crises, which involves the formation of insurance funds at the expense of insurance premiums of legal and natural persons and their subsequent use in compensation for damages caused by the occurrence of insurance events